Global and Local Manipulation of DNA Repair Mechanisms to Alter Site-Specific Gene Editing Outcomes in Hematopoietic Stem Cells - Benitez, Elizabeth K.; Lomova Kaufman, Anastasia; Cervantes, Lilibeth; Clark, Danielle N.; Ayoub, Paul G.; Senadheera, Shantha; Osborne, Kyle; Sanchez, Julie M.; Crisostomo, Ralph Valentine; Wang, Xiaoyan; Reuven, Nina; Shaul, Yosef; et al. (Frontiers in Genome Editing, 2020)
Monogenic disorders of the blood system have the potential to be treated by autologous stem cell transplantation of ex vivo genetically modified hematopoietic stem and progenitor cells (HSPCs). The sgRNA/Cas9 system allows for precise modification of the genome at single nucleotide resolution. However, the system is reliant on endogenous cellular DNA repair mechanisms to mend a Cas9-induced double stranded break (DSB), either by the non-homologous end joining (NHEJ) pathway or by the cell-cycle regulated homology-directed repair (HDR) pathway. Here, we describe a panel of ectopically expressed DNA repair factors and Cas9 variants assessed for their ability to promote gene correction by HDR or inhibit gene disruption by NHEJ at the HBB locus. Although transient global overexpression of DNA repair factors did not improve the frequency of gene correction in primary HSPCs, localization of factors to the DSB by fusion to the Cas9 protein did alter repair outcomes towards microhomology-mediated end joining (MMEJ) repair, an HDR event. This strategy may be useful when predictable gene editing outcomes are imperative for therapeutic success.